The Responsibility of State Administrative Officials in the Implementation of the Decisions of the State Administrative Court - Zainuddin, Zainuddin (International Journal Reglement & Society (IJRS), 2020)
Decisions of State and Government administration, namely decisions made by Government Agencies, either regulating (regression) or beschikking. Making judgments is a legal act. This research uses normative juridical legal research methods (normative research) with descriptive analytical research specifications that use secondary data. The data collection procedure is in the form of documentation of notes or quotations, tracing legal literature, books and others related to identification of problems both offline and online which are then analyzed through the content analysis method (centent analysis method) with a focus on the problem of how the factors inhibiting the implementation of the injunction of state administrative court decisions and how the responsibility of state administrative officials to the implementation of administrative court decisions state effort. That the factors inhibiting the implementation of court decisions that are legally enforceable include: The absence of a special executorial institution or sanction institution that functions to implement decisions. The low level of awareness of State Administration officials in obeying the decisions of the State Administrative Court. There is no stricter regulation regarding the implementation of the decision of the State Administrative Court